(untitled) (Nordic Journal of Practical Theology, 2025)
Like other civic organizations, the Evangelical Lutheran Church of Norway extensively engages volunteers. This article presents findings from a survey among church employees who lead volunteers. It aims to determine which leadership practices are in use, whether leadership is conducted in a values-conscious way, and the prevalence and use of strategic plans for voluntary work. The research question is: To what extent do employees in the Church of Norway utilize leadership practices identified in Sporsheim and Sirris’ (2018) model for church volunteer leadership? A total of 89 employees in the dioceses of Oslo and Stavanger responded to a questionnaire. Our data show that practices such as facilitating and informing are prioritized over leading and motivating. We find a high degree of values consciousness, reflected both in the prevalence of congregational core values and in respondents articulating and expressing them. Plans and structures for voluntary work are less well developed and lack a cohesive profile. There are only small variations between the dioceses and professional groups.